Tumor microcalcification-mediated relay drug delivery for photodynamic immunotherapy of breast cancer. (1st March 2022) - Jian, Hui; Wang, Xingbo; Song, PanPan; Wu, Xiaqing; Zheng, Runxiao; Wang, Yanjing; Zhang, Haiyuan
Abstract: Spatiotemporal targeting of tumor-associated macrophages (TAMs) and tumor cells is emerging as a promising strategy for tumor therapy. Tumor microcalcifications that specifically bind to bisphosphonates are potentially used to design efficient relay drug delivery nanosystems to achieve spatiotemporal drug modulation. Here, we developed manganese dioxide (MnO2 )-embedded and LyP-1 peptide-labeled liposomal nanoparticles (NPs) for photodynamic immunotherapy of breast cancer; zoledronic acid (Zol) was encapsulated in the hydrophilic cavity of liposomes, and a hydrophobic photosensitizer (IR780) was embedded in the phospholipid bilayer of liposomes. These Lipo Zol/IR NPs generated O2 bubbles through MnO2 in response to H2 O2 in the tumor microenvironment, leading to the degradation of the liposomal membrane, which triggered the release of Zol and provided O2 for photodynamic therapy. The released Zol attached to microcalcifications and was selectively phagocytosed by TAMs, leading to the induction of death or repolarization of TAMs from the immunosuppressive M2 phenotype to the immunostimulatory M1 phenotype. The remaining liposomal fragments embedded with IR780 then preferentially targeted tumor cells through LyP-1 peptide and produced abundant reactive oxygen species (ROS) under near infrared (NIR) laser irradiation, resulting in the death of tumor cells and mild immune activation. All in vitro and in vivo studies demonstrated the effective photodynamic and immunoregulatory performance of Lipo Zol/IR NPs. Statement of significance: Spatiotemporal targeting of tumor-associated macrophages (TAMs) and tumor cells remains a challenge in tumor photodynamic immunotherapy for promoting synergy and reducing side effects. Here, we developed tumor microcalcification-mediated relay drug delivery nanoliposomes for breast cancer therapy. H2 O2 in the tumor microenvironment (TME) triggers the breakage of nanoliposomes, thereby causing the separation of zoledronic acid (Zol) and the photosensitizer IR780 and allowing them to perform their respective functions. Microcalcifications enable Zol to target TAMs, resulting in immunomodulation. LyP-1 guides IR780 to target tumor cells for PDT with adequate O2 supply. These nanoliposomes enable precise spatiotemporal targeting of different types of cells in the TME and promote the synergy between immunotherapy and PDT while ensuring the effectiveness of both methods. Graphical abstract: Image, graphical abstract